Stock Price Behavior of Nepalese Commercial Banks: Random Walk Hypothesis - Bam, Nirajan; Thagurathi, Rajesh Kumar; Shrestha, Bipin (Journal of Business and Management, 2018)
Using the data set on daily stock prices during the fiscal year 2015/16 (Sept 23, 2015 through Dec 22, 2015), this paper attempts to analyze the random behavior of stock price of Nepalese Commercial Banks by using run test, serial correlation and run tests and martingale random walk hypothesis under heteroscedasticity assumption of standard error. The results conclude that the proposition of Random Walk Hypothesis (RWH) in Nepalese stock markets does not hold true. This conclusion corroborates with the conclusions of the past studies carried out in Nepalese context.